2011
DOI: 10.1007/s12170-011-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicrons: A Key Biomarker and Risk Factor for Cardiovascular Disease and for the Understanding of Obesity

Abstract: Cardiovascular disease can be considered a condition of chronic low-grade inflammation. Postprandial hyperlipidemia and obesity can both exacerbate inflammatory processes. Postprandial lipemia stimulates the activation of leukocytes, the production of chemokines, and activation of the complement system. Obesity is also associated with postprandial hyperlipidemia by hepatic overproduction of very low-density lipoprotein (VLDL) and consequently delayed clearance of intestinally derived chylomicrons due to compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 78 publications
(77 reference statements)
1
16
0
Order By: Relevance
“…Small dense LDL have an increased affinity for arterial proteoglycans resulting in enhanced subendothelial lipoprotein retention [58]. However, subendothelial remnants of chylomicrons and VLDL do not need to become modified to allow uptake by scavenger receptors of macrophages in contrast to native LDL [59]. It has been described that small dense LDL are more susceptible for oxidation, in part due to less free cholesterol and anti-oxidative content [60].…”
Section: Obesity Induced Changes In Lipoprotein Metabolism and Athmentioning
confidence: 99%
See 2 more Smart Citations
“…Small dense LDL have an increased affinity for arterial proteoglycans resulting in enhanced subendothelial lipoprotein retention [58]. However, subendothelial remnants of chylomicrons and VLDL do not need to become modified to allow uptake by scavenger receptors of macrophages in contrast to native LDL [59]. It has been described that small dense LDL are more susceptible for oxidation, in part due to less free cholesterol and anti-oxidative content [60].…”
Section: Obesity Induced Changes In Lipoprotein Metabolism and Athmentioning
confidence: 99%
“…Several investigators have demonstrated an association between TG-rich lipoproteins and remnant cholesterol levels with the presence of coronary [34,35,36,38,39,40,41,42,68], cerebral [37], and peripheral atherosclerosis [69]. In addition to a direct detrimental effect by chylomicron remnants on vessels [59], impaired endothelial function after an oral fat load [70] and after infusion of artificial TG-rich lipoproteins have been described [71]. This phenomenon may take place by elevated levels of FFA [72], which are generated by the action of LPL mediated lipolysis.…”
Section: Obesity Induced Changes In Lipoprotein Metabolism and Athmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity will eventually develop upon a high fat, hypercaloric diet, which contributes to the development of hypertriglyceridemia [31]. The relationship between obesity, alcohol and plasma triglycerides was confirmed in an experimental study, where participants consumed 250 ml red wine during 14 days [34 & ].…”
Section: Interaction Between Lifestyle Alcohol and Plasma Triglyceridesmentioning
confidence: 99%
“…Lifestyle factors, like dietary fat consumption, body weight, smoking and physical exercise, influence plasma triglycerides as well [31,32]. Alcohol consumption can exaggerate the hypertriglyceridemia associated with an unhealthy lifestyle [7], but alcohol consumption is also related to an unhealthy diet [5].…”
Section: Interaction Between Lifestyle Alcohol and Plasma Triglyceridesmentioning
confidence: 99%